2003
DOI: 10.1046/j.1540-8167.2003.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose‐Induced Insulin Secretion on ST Segment Elevation in the Brugada Syndrome

Abstract: Introduction: ST segment elevation in patients with Brugada syndrome is known to fluctuate occasionally, influenced by multiple factors. Insulin has been shown to affect QT dispersion in healthy volunteers, as well as result in abnormality of ventricular repolarization in patients with congenital long QT syndrome. Methods and Results: To assess a possible role of insulin in ST segment elevation in patients with Brugada syndrome, an oral glucose tolerance test (OGTT) was administered to 20 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 22 publications
2
46
2
Order By: Relevance
“…Another study by Nishizaki assessed oral glucose tolerance test (OGTT) in Brugada syndrome patients and control healthy subjects. They found Glucose-induced insulin secretion lead to ST-segment elevation and induce ECG morphologic changes only in patients whereas BG, insulin level and K + level were not significantly different between two groups [16]. Ikeda et al [26] demonstrated that the augmentation of STsegment elevation was associated with a stomach rapidly filled with a large meal [26].…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study by Nishizaki assessed oral glucose tolerance test (OGTT) in Brugada syndrome patients and control healthy subjects. They found Glucose-induced insulin secretion lead to ST-segment elevation and induce ECG morphologic changes only in patients whereas BG, insulin level and K + level were not significantly different between two groups [16]. Ikeda et al [26] demonstrated that the augmentation of STsegment elevation was associated with a stomach rapidly filled with a large meal [26].…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 98%
“…However, the study of Nishizaki and co-workers found serum K + concentrations were unchanged after the glucose load. They still proposed the possibility that increased K + gradient could affect the repolarization process differently among the three regions of the ventricular walls (endocardium, epicardium and myocardium) cannot be excluded and might contribute to the ST-segment abnormalities observed in patients with Brugada syndrome [16].…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 99%
“…stomach, fever, glucose insulin test, etc. [17][18][19][20]22,26 ) caused ECG alterations in the patients, we emphasize that spontaneous ECG alterations without any stress often occurred in the patients with a high risk of VF. Patients who had long-term ECG alterations also were likely to have spontaneous AP heterogeneity that causes ECG alterations and VF.…”
Section: Changing Ecgs In Bsmentioning
confidence: 75%
“…Hypokalemia and insulin secretion cause ST segment changes in patients with Brugada syndrome. 2,4) Humoral regulation from alcohol intake may be related to the induction of VF in this case. In addition, it was recently reported that alcohol has an inhibitory effect on single cardiac sodium channel gating.…”
Section: Discussionmentioning
confidence: 88%